Effects and trend of steroid dosage reduction during cardiac surgery: A three-year retrospective analysis at a tertiary medical center - Jeng-Wei Chen; Hsiu-Wen Liang; Bo-Wei Fong; Chih-Yang Chan; Heng-Wen Chou; Nai-Kuan Chou; Chih-Hsien Wang; Nai-Hsin Chi; I-Hui Wu; Shu-Chien Huang; Hsi-Yu Yu; Yih-Sharng Chen; et al. (Journal of the Formosan Medical Association)
Background: Current adult cardiac surgery guidelines recommend against the routine use of prophylactic intravenous corticosteroids during cardiopulmonary bypass (CPB) due to concerns about myocardial injury, despite their potential to reduce postoperative atrial fibrillation. Traditionally, a high dose of 1,000 mg of methylprednisolone was used to attenuate the inflammatory response associated with CPB. Our institution aligned with guideline recommendations and gradually reduced methylprednisolone dosages; thus, we reevaluated the impact on postoperative clinical outcomes. Methods: Our study reviewed 1341 cases from a total of 1680 adult cardiac surgeries performed between June 2019 and May 2022 after excluding cases with off-pump procedures, ventricular assist device implantations, heart transplants, and aortic surgeries requiring systemic circulatory arrest. The study timely sorted periods including a baseline data from 2018, and other three periods since 2019 to analyze the effects of three different methylprednisolone dosage: 0 mg, 500 mg, and 1000 mg. We assessed the annual trends in methylprednisolone administration and compared morbidity and mortality rates across the groups. Results: We observed a significant decline in steroid use, with no-steroid surgeries increasing from 23% to 66.5% by period 3. Despite the decreased use of steroids, our study showed no increase in mortality, new-onset atrial fibrillation, acute kidney injury, cerebrovascular event and prolonged ventilation when compared to baseline data. Notably, less surgical site infection rate was observed in the no-steroid group. Conclusion: The data indicates that a reduction or discontinuation of steroids during CPB can be performed without compromising patient outcomes. This could support a transition towards a more conservative use of steroids in adult cardiac surgery, aligning with current guidelines, and potentially reducing certain postoperative complications.